2017
DOI: 10.1039/c7cc07554e
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed [2+2+2+2]-annulation of 1,3,5-hexahydro-1,3,5-triazines with alkoxyallenes

Abstract: An unprecedented gold-catalyzed [2+2+2+2]-annulation of 1,3,5-hexahydro-1,3,5-triazines with alkoxyallenes has been developed, providing eight-membered heterocycles in good to excellent yields. Deuterium labeling and control experiments reveal the possible reaction mechanism for this annulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
27
0
2
Order By: Relevance
“…In addition to the utilization of 1,3,5‐triazines as Mannich reagents in aminomethylation protocols, they could also serve as efficient 1,4‐dipoles or 1,2‐dipoles in the construction of biologically important N‐containing heterocyclic ring structures through cycloaddition . Representative examples including the [3+2] cycloaddition, [2+1+2] cycloaddition, [2+2+2] cycloaddition, [3+2+2] cycloaddition, [4+3] cycloaddition, [2+2+2+2] cycloaddition, and [4+1]/[4+3] cycloaddition, were sequentially investigated as valuable cycloaddition reactions for the synthesis or modification of drug or drug‐like complex heterocyclic molecules. Compared with these well‐developed types of cycloaddition processes, [4+2]‐cycloaddition reactions with 1,3,5‐triazines acting as the 1,2‐dipoles have been relatively less investigated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the utilization of 1,3,5‐triazines as Mannich reagents in aminomethylation protocols, they could also serve as efficient 1,4‐dipoles or 1,2‐dipoles in the construction of biologically important N‐containing heterocyclic ring structures through cycloaddition . Representative examples including the [3+2] cycloaddition, [2+1+2] cycloaddition, [2+2+2] cycloaddition, [3+2+2] cycloaddition, [4+3] cycloaddition, [2+2+2+2] cycloaddition, and [4+1]/[4+3] cycloaddition, were sequentially investigated as valuable cycloaddition reactions for the synthesis or modification of drug or drug‐like complex heterocyclic molecules. Compared with these well‐developed types of cycloaddition processes, [4+2]‐cycloaddition reactions with 1,3,5‐triazines acting as the 1,2‐dipoles have been relatively less investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, the Sun group revealed that gold catalysis also enabled a novel [2+2+2+2]-annulation reaction between 1,3,5-triazinanes 2 and alkoxyallenes 57, providing eight-membered heterocycles 58 in good to excellent yields (Scheme 26a). 30 In their previous study, the gold-catalyzed reaction of allenamides with 1,3,5-triazinanes in a 1:1 ratio resulted in the formation of only six-membered heterocycles. 28 However, as shown in Scheme 26b, one equivalent of 2c and 57a yielded 58a and 58a′ in 43% and 56% yields, respectively.…”
Section: Scheme 25 Gold-catalyzed [2+2+2]-cycloaddition Reactions Betmentioning
confidence: 99%
“…[13] Subsequently, Feng [14] and Kang [15] reported the asymmetric Mannich reaction of 1,3,5-triazinanes, respectively. [23] In addition, Werz [21] and later also our group [24] reported the [3 + 2] cycloaddition of 1,3,5-triazinanes to access pyrrolidines, respectively. [23] In addition, Werz [21] and later also our group [24] reported the [3 + 2] cycloaddition of 1,3,5-triazinanes to access pyrrolidines, respectively.…”
mentioning
confidence: 98%